The Effect of Context on Understanding Phrasal Verbs and their Avoidance by Students of University of Anbar - Hayif Sameer , Imad; Mohammed Abd-Razaq, Ghassan (International Journal of Psychosocial Rehabilitation, 2020)
Schachter (1974) focuses on the importance of error analysis for examining not only to find out the most common errors committed by learners of foreign languages but to circle the items or expressions avoided by them. This avoidance is due in most cases to the close interrelation between such avoidance phenomena and the Contrastive Analysis approach between the mother tongue and the target. Kleinmann (1977) assures that “avoidance” means that the learners have an idea about the structure in question but they do not have the ability to use it actively and correctly. Phrasal verbs that are part of multiword expressions pose a difficulty to Iraqi learners, especially to students of the University of Anbar/Department of English/College of Education for Humanities. This difficulty is logical because most Iraqi speakers avoid dealing with the components of this category. Most of the students who form the sample of the study, which consists of 30 students (15 males and 15 females), have an idea about the meaning of the phrasal verbs (give up, switch off, and switch on) because they are highly used in Iraqi culture. The study shows that the sample in the question faces difficulty using this category. The aim of this article is to clarify the factors that have an effect on understanding the components of this category. It hypothesizes that the members of the sample can depend on the context to extract the correct meaning of phrasal verbs, and without it they cannot understand their meaning. They, in most cases, avoid using them and resort to single words. Three tests are conducted to achieve the aim and prove the hypotheses. The first one clarifies the role of the context in determining the exact meaning of phrasal verbs, while the second shows the difficulties that face students in dealing with this category. The third test manifests the avoidance of students to use them.